1996
DOI: 10.4319/lo.1996.41.1.0089
|View full text |Cite
|
Sign up to set email alerts
|

Growth, iron requirements, and siderophore production in iron‐limited Synechococcus PCC 72

Abstract: We have investigated the changes associated with growth over a range of iron availabilities in the cyanobacterium Synechococcus PCC 7002. This cyanobacterium compensates for growth-limiting levels of iron availability by decreasing its maximum growth rate, cellular pigment levels, and apparent iron requirements. This organism also releases extracellular siderophores, which facilitate the acquisition of iron that was previously biologically unavailable from the extracellular environment. Our results suggest a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 25 publications
8
74
1
Order By: Relevance
“…It is realised that these extremely low values are biased by taking in account only dissolved Fe concentrations, ignoring kinetics of Fe. In the case of Synechococcus, cellular iron values were reported to vary over 4 orders of magnitude with changing ambient iron concentration (Wilhelm et al, 1996). A dtrueT estimate of the iron content of Synechococcus was achieved using continuous cultures resulting in an iron quotum of 0.42 Â 10 À18 M cell À1 (Wilhelm and Trick, 1995), about 100 times higher than the value reported for Synechococcus in this study.…”
Section: Fe Limitation Experimentsmentioning
confidence: 44%
See 1 more Smart Citation
“…It is realised that these extremely low values are biased by taking in account only dissolved Fe concentrations, ignoring kinetics of Fe. In the case of Synechococcus, cellular iron values were reported to vary over 4 orders of magnitude with changing ambient iron concentration (Wilhelm et al, 1996). A dtrueT estimate of the iron content of Synechococcus was achieved using continuous cultures resulting in an iron quotum of 0.42 Â 10 À18 M cell À1 (Wilhelm and Trick, 1995), about 100 times higher than the value reported for Synechococcus in this study.…”
Section: Fe Limitation Experimentsmentioning
confidence: 44%
“…Measurements of Fe iron quota in pico-phytoplankton are scarce and hindered by technical complications, as for example Fe adsorbed externally (Wilhelm et al, 1996), and/or the inability to measure the concentration and kinetics of the bioavailable iron pool. Minimum Fe quota (only for cultures grown at Fe replete conditions) in the three species that we tested during our study were extremely low, in the zepto-mol (10 À21 mol) cell À1 range (Table 3).…”
Section: Fe Limitation Experimentsmentioning
confidence: 99%
“…Utilization of a standardized Redfield ratio allows for an intercomparison of results (Table 1). These requirements can be contrasted with those determined through the utilization of a solution of titanium (111)-citrate-EDTA (Hudson & More1 1989), which rapidly reduces extracellular iron and allows for a determination of iron within the cell when cells are maintained with tracer levels of ' ' Fe or jgFe (Sunda et al 1991, Wilhelm et al 1996. In all cases, cyanobactenal Fe requirements are higher than those of eukaryotic algae (Table 1).…”
Section: Effect Of Iron Availability On Cyanobacterial Growthmentioning
confidence: 95%
“…PCC 7002 (Wilhelm & Trick 1995a). Boussiba & Richmond (1980) have suggested that the degradation of cellular phycocyanin may be only a secondary effect of iron limitation; nitrogen deficiency caused by a reduction in the level of iron-containing enzymes required for nitrogen assimilation may cause the cells to degrade phycocyanin pools and utilize them as a source of N. Decreases have also been documented for cellular levels of the accessory pigments zeaxanthin and p-carotene (Wilhelm et al 1996).…”
Section: Iron-limited Cyanobacterial Physiologymentioning
confidence: 99%
“…This method is relatively simple, with only one time point, but the metal uptake kinetics cannot be obtained nor can cell surface adsorption, which is completed within a few minutes (Hassler et al 2004). The cells can also excrete some metabolites during the long-term exposure period; thus, the water chemistry and metal speciation might be affected, which are critical in metal accumulation (Wilhelm et al 1996;Marañón et al 2004;Wei and Ahner 2005). In the short-term exposure experiments, cellular metal accumulation is quantified at dif-1 Corresponding author (wwang@ust.hk).…”
mentioning
confidence: 99%